The Sensitivity of Labor Demand Functions to Choice of Dependent Variable - Borjas, George J. (The Review of Economics and Statistics, 1986)
This paper investigates whether the parameters of labor demand functions are sensitive to alternative methods of estimation.The assumption that the production technology is of the Generalized Leontief type implies that the demand system can be estimated by analyzing cross-section differences in earnings across labor markets, by studying longitudinal changes in earnings within a labor market, or by investigating cross-section differences in labor force participation rates across labor markets.The estimation of these models on the 1970 and 1980 Public Use Samples from the U.S. Census reveals that the estimates of labor demand functions are indeed quite robust to major specification changes.